2021
DOI: 10.1097/md.0000000000025398
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of gemcitabine-based induction chemotherapy for locally advanced nasopharyngeal carcinoma treated with concurrent chemoradiation

Abstract: Objectives: To assess the efficacy and toxicity of gemcitabine-based induction chemotherapy followed by concurrent chemoradiotherapy (CCRT) in locally advanced nasopharyngeal carcinoma (LA-NPC). Methods: Both observational studies (OBS) and randomized controlled trials (RCT) were included in the meta-analysis. Systematic online searches were conducted in Web of Sciences, PubMed, Embase, meeting proceedings and ClinicalTrials.gov from the inception to May 25, 2020. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 39 publications
2
3
0
Order By: Relevance
“…Therefore, the treatment side effects and other related profiles are not revealed in the results. However, the current meta‐analytic results reconfirmed the significant benefits for survival of patients with locoregionally advanced NPC seen in previous meta‐analyses 26–35 . Therefore, the benefits of ICT for the survival condition of locoregionally advanced NPC might be consistent and persuasive.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…Therefore, the treatment side effects and other related profiles are not revealed in the results. However, the current meta‐analytic results reconfirmed the significant benefits for survival of patients with locoregionally advanced NPC seen in previous meta‐analyses 26–35 . Therefore, the benefits of ICT for the survival condition of locoregionally advanced NPC might be consistent and persuasive.…”
Section: Discussionsupporting
confidence: 79%
“…[27][28][29] In addition, our meta-analysis purely focused on randomized controlled trials, which minimizes bias from retrospective studies or cohort studies as found in other meta-analyses. [32][33][34] The consistent and significant benefits of the OS, PFS, DMFS, and LRRFS seen here underscore the advantages of applying ICT for locoregionally advanced NPC patients. However, different regiments of T A B L E 1 (Continued) ICT in these studies should be considered when interpreting the meta-analysis results.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations